Analisis Efektivitas dan Efisiensi Penerapan E-Tax Invoice Dalam Penerbitan Faktur Pada PT Syma Berkah Indonesia - Rizma Fatmawati Putri; Siti Sundari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to discuss the effectiveness and efficiency of E-Tax Invoice in issuing invoices at PT Syma Berkah Indonesia. The core discussion discussed in this research is the level of effectiveness and efficiency of E-Tax Invoice in issuing invoices. This research was conducted at PT Syma Berkah Indonesia using descriptive qualitative methods and data collection techniques using interviews and observation. To find out the actual situation, interview administration and accounting managers and observe for 5 months. Based on the research results, it shows that the implementation of E-Tax Invoice in issuing invoices at PT Syma Berkah Indonesia has not reached the expected level of effectiveness and efficiency. The causal factors are limited human resources, busyness and access of the main director, lack of understanding and training of administrative managers and finances in using E-Tax Invoice.